2018
DOI: 10.1186/s12879-018-3194-6
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and risk factors of recent infection with hepatitis E virus during an acute outbreak in an urban setting in Chad, 2017

Abstract: BackgroundFrom September 2016–April 2017, Am Timan, Chad, experienced a large HEV outbreak in an urban setting with a limited impact in terms of morbidity and mortality. To better understand HEV epidemiology in this context, we estimated the seroprevalence of anti-HEV antibodies (IgM and IgG) and assessed the risk factors for recent HEV infections (positive anti-HEV IgM) during this outbreak.MethodsA serological survey using simple random sampling was implemented in Am Timan at the tail-end of the outbreak (sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 22 publications
0
11
1
Order By: Relevance
“…We observed evidence of protective immunity during our analysis of immunoprevalence where participants were found to have very high antibody levels in the baseline (S1) samples which were indicative of prior exposures (9) most without complaints of the symptoms of gastrointestinal illness (15). This phenomenon of high underlying immunity in a population is not uncommon and as a recent example, was observed during an outbreak of hepatitis E virus in Chad (33).…”
Section: Discussionmentioning
confidence: 87%
“…We observed evidence of protective immunity during our analysis of immunoprevalence where participants were found to have very high antibody levels in the baseline (S1) samples which were indicative of prior exposures (9) most without complaints of the symptoms of gastrointestinal illness (15). This phenomenon of high underlying immunity in a population is not uncommon and as a recent example, was observed during an outbreak of hepatitis E virus in Chad (33).…”
Section: Discussionmentioning
confidence: 87%
“…Given the logistical challenges of delivering three doses over a six month period, future research to better quantify the value of one and two doses of vaccine and perhaps a reduced interval between doses 2 and 3 would be valuable. Finally, it is not clear how relevant the modelling framework used here will be for community outbreaks where HEV is already endemic, such as the recent urban outbreak in Chad [ 37 ]; further work is needed to evaluate the potential impact of hepatitis E vaccination in different contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Data on risk factors for HEV infection (defined by IgM antibodies or RNA), disease, and death were identified in 36 studies (17,21,26,30,34,46,63,68,74,85,91,92,102,104,(108)(109)(110)112,116,129,138,139,(145)(146)(147)(148)(149)(150)(151)(152)(153)(154)(155)(156)(157)(158) from 13 countries between 1990 and 2017. One study only reported risk factors with an unknown hypothesized direction of effect and was excluded from further analysis (159).…”
Section: Risk Factorsmentioning
confidence: 99%
“…Excludes 18 seroprevalence studies with unspecified study year.Among studies that reported assay manufacturer (85%; 77/91), anti-HEV IgG antibodies were assessed using 18 different commercial assays as well as in-house assays (e.g.Walter Reed Army Institute of Research in-house assay). The most common assaysused to assess seroprevalence were in-house assays (21%)(14,34,44,47,51,53,56,60,61,70,72,79,84,91,97,100), Wantai (18%; Wantai BioPharm, Beijing, China)(20)(21)(22)(23)31,40,46,48,54,59,63,65,76,77), and Abbott (14%; (Abbott Diagnostika, Germany)(15,18,28,32,43,80,82,83,87,93,94) with the Wantai assay becoming the most commonly used assay in studies conducted in the last 5 years of the review (2013-2017).…”
mentioning
confidence: 99%